Afterword: The Urban and the Carceral. Issue 1 (1st March 2020) - Jensen, Steffen
Abstract: In this afterword, I consider some of the important insights that are generated in this special issue. The thorough and detailed consideration of the ways in which detainees and formerly incarcerated persons survive confinement and the constraints imposed on them illustrates the power of ethnography. Each of the contributions builds on strong empirical material and sometimes decade-long engagement with people in and on the brink of confining institutions. In this way, the contributions form a comprehensive empirical foundation for understanding confinement beyond the carceral institutions, while also allowing us to ask new kinds of questions about confinement beyond site. While firmly rooted in prison ethnography, the special issue thus inspires urban studies and anthropologists more broadly to think concertedly about the role of confinement, not only as the fate of many urban residents but as an ever-present element of the urban imaginary and of urban life.